Excellence board of public housing in the Netherlands through a coherent set of values. (2017) - Veuger, Jan
Housing associations make too small a contribution to society, the government has to step in too frequently because of maladministration, and the associations' executives are often unaware of the far-reaching impact of their decisions. These are the conclusions of new academic research conducted by Jan Veuger of Rotterdam School of Management, Erasmus University (RSM). In his dissertation, he asserts that in numerous cases there is no correlation between social and financial objectives. After extensive exploration of the literature and PhD studies the research design inspired based on the grounded theory, which has a certain bias as a result of the extensive literature study. My contribution to science is also showing patterns of board behaviour, whether or not in conjunction with societal and financial values of housing associations. This contribution complements studies on the culture of housing associations (Dreimüller, 2008; Sinke, 2014) or only driver behavior (Heemskerk, 2013) or history of housing corporations (Beekers, 2012) or about the behaviour of housing associations (Koolma, 2009).